Cross-Time-Frequency Analysis of Volatility Interdependence among Stock and Currency Markets - Baklaci, Hasan Fehmi; Yelkenci, Tezer (The Economics and Finance Letters, 2020)
Volatility transmission between stock markets and currency markets is an ongoing debate in the pertinent literature. However, the majority of the previous studies have used only daily data with a limited sample. This study aims to fill this gap by identifying how sample stock markets and currencies play the role of volatility transmitter and receiver, particularly on an intraday basis. To this end, this research detects volatility interdependencies among various stock markets and currencies using five major stock indices and six major currency pairs. The results for daily and intraday frequencies are quite disparate. In particular, the results signify that the transmission of volatility from currency markets to stock markets is much stronger on an intraday basis. The results also indicate a strengthening of the volatility transmission and spillover interdependence among stock markets on a daily basis. These results may be ascribed to the continuous trading mechanism of these markets, which in turn allows the news to impact these markets first, which then transmit it to stock markets. The findings obtained also imply that intraday price fluctuations in major currencies should be closely tracked to monitor intraday volatility patterns in stock markets.